Evolusi social commerce: Memahami Fenomena Digital melalui Perspektif Teori Komunikasi dan Sosial - Yuwono, Claudia Oktaviani; Rizky, Nifirinas Yulistin; Indra, Intan Rosma (Syntax Corporation, 2025)
Indonesian people are among the largest users of social media. There are 139 million users out of a total population of 278.7 million. From the age range of social media users from 15-40 years old and above. The various social media functions offered make people dependent on various social media. The most widely used applications are WhatsApp, Instagram, X, Tiktok and Youtube. Currently, social media that presents a short video format is more popular. The purpose of this research is to discuss social interactions that occur in social commerce, namely Tiktok Shop by using several communication theories in the context of society according to Littlejohn, et al. The theory that will be discussed is the diffusion of innovation to see how Tiktokshop is adapted by the community. Then the theory of symbolic interactionism is to see how user interaction, as well as existing content, forms the meaning of objects that are often talked about in social commerce and become viral. Then the theory continues the social construction to see how interaction in the Tiktok Shop constructs the fear of missing out (FoMO) which can encourage consumers to buy without careful consideration. So, when understanding this phenomenon through the perspective of communication theories such as innovation diffusion, symbolic interactionism, and social construction, readers can see the opportunities and challenges of social commerce in shaping a more inclusive, transparent, and responsible digital culture.